HERC 1 Ubiquitin Ligase Mutation Affects Neocortical, CA3 Hippocampal and Spinal Cord Projection Neurons: An Ultrastructural Study - Ruiz, Rocío; Pérez-Villegas, Eva María; Bachiller, Sara; Rosa, José Luis; Armengol, José Angel (Frontiers in Neuroanatomy, 2016)
The spontaneous mutation tambaleante is caused by the Gly483Glu substitution in the highly conserved N terminal RCC1-like domain of the HERC1 protein, which leads to the increase of mutated protein levels responsible for cerebellar Purkinje cell death by autophagy. Until now, Purkinje cells have been the only central nervous neurons reported as being targeted by the mutation, and their degeneration elicits an ataxic syndrome in adult mutant mice. However, the ultrastructural analysis performed here demonstrates that signs of autophagy, such as autophagosomes, lysosomes, and altered mitochondria, are present in neocortical pyramidal, CA3 hippocampal pyramidal, and spinal cord motor neurons. The main difference is that the reduction in the number of neurons affected in the tambaleante mutation in the neocortex, the hippocampus, and the spinal cord is not so evident as the dramatic loss of cerebellar Purkinje cells. Interestingly, signs of autophagy are absent in both interneurons and neuroglia cells. Affected neurons have in common that they are projection neurons which receive strong and varied synaptic inputs, and possess the highest degree of neuronal activity. Therefore, because the integrity of the ubiquitin-proteasome system is essential for protein degradation and, hence, for normal protein turnover, it could be hypothesized that the deleterious effects of the misrouting of these pathways would depend directly on the neuronal activity.